Genome-Wide Identification, Characterization, and Expression Pattern Analysis of the JAZ Gene Family in Wax Apple (Syzygium samarangense) - Liang Li; Weijie Huang; Limei Tang; Ling Xu; Yajun Tang; Xiuqing Wei; Jiahui Xu (Horticulturae)
Wax apple (Syzygium samarangense) is a characteristic tropical fruit with great potential value, but the cold sensitivity and male sterility limit its cultivation and breeding. Despite the important role in JA-mediated cold-stress resistance and flower development, jasmonate ZIM-domain (JAZ) proteins have not been identified in wax apple. This study employed sequence blast, phylogenetic analysis, and RT-PCR to identify SsJAZs in wax apple systematically. First, 14 SsJAZs family members with TIFY and Jas domains were identified and named according to the distribution on ten chromosomes. Low-temperature responsiveness elements and TGACG-motif (response to MeJA) were abundant in the promoters of most SsJAZs. The transcription factors ERF and MYB were predicted to be involved in the regulation of SsJAZs. RT-PCR analyses showed that SsJAZs were mainly expressed in mature leaves and flowers. Further analysis revealed differences in the expression patterns of SsJAZs under cold treatment, as well as in different anther stages. SsJAZ proteins were predicted to interact with the N terminus of SsMYC2 protein via the Jas motif at the C-terminal domain. This study characterized the SsJAZs family members and examined the expression patterns in different samples. The results will advance our understanding of the role of SsJAZs in wax apple.